Association of physical function, anxiety, and pain interference in non-shoulder upper extremity patients using the PROMIS platform - Kazmers, Nikolas H. (J Hand Surg Am, 2017)
PURPOSE: The relationship between psychosocial factors and self-reported physical function among hand and upper extremity patients is complex. The Patient-Reported Outcomes Measurement Information System (PROMIS) platform has attempted to create a variety of specifically-targeted metrics which can be administered using computer adaptive testing (CAT). Three metrics measuring self-reported physical function (herein referred to in combination as “functional” metrics) include the PROMIS Physical Function (PF) CAT, PROMIS Upper Extremity (UE) CAT, and the quick-Dash (qDASH). Two metrics assessing psychosocial factors include the PROMIS Anxiety and Pain Interference (PI) CATs (“non-functional” metrics). This study evaluates whether the functional metrics were correlated with non-functional metrics. METHODS: The five questionnaires were administered prospectively on a tablet computer to all consecutive adult patients presenting to outpatient hand and upper extremity (non-shoulder) clinic at a tertiary academic medical center from 1/1/2014 – 11/1/2014. For patients with multiple visits during the study period, only the first was included. Data were evaluated retrospectively to assess the relationship between functional and non-functional measures, with Pearson correlation coefficients to understand the relationship between continuous variables, and one-way ANOVAs to examine for differences in outcome measures across demographic groups. Multivariable linear regression analyses were performed to determine factors predicting functional disability. RESULTS: We included 1299 patients: mean age was 46.8 years, 53% were female, and 23% were unemployed or on disability. The PROMIS PF CAT, PROMIS UE CAT, and qDASH scores were all significantly correlated with PROMIS Anxiety CAT (Pearson correlation coefficients −0.46, −0.48, and 0.53, respectively) and PROMIS PI CAT (−0.60, −0.65, and 0.76, respectively) scores. Multivariable regression analyses demonstrated that increased PROMIS Anxiety and Pain Interference CAT scores each independently and adversely influenced PROMIS PF CAT, PROMIS UE CAT, and qDASH scores. CONCLUSIONS: Increasing levels of patient anxiety and pain interference are independently associated with decreased patient-reported upper extremity function. CLINICAL RELEVANCE STATEMENT: This study provides further support of the biopsychosocial model by highlighting that increased anxiety is associated with decreased self-reported function using the PROMIS platform.